A measure for perioperative anxiety symptoms in patients with FUAS - treated uterine fibroids: development and validation. (31st December 2022) - Zhang, Xin; Xu, Wei; Sang, Guowei; Yu, Dan; Shi, Qiuling
Abstract: Objective: To develop a scale that measured the perioperative anxiety symptoms of uterine fibroids (PASM-UF) treated with focused ultrasound ablation surgery (FUAS). Methods: A panel of gynecologists, nurses, and patient-reported outcome (PRO) experts created a draft of the PASM-UF scale. Women who underwent FUAS for uterine fibroids were recruited for its psychometric validation. Assessments were conducted during admission, before surgery, and at discharge. The Symptom Checklist-90 (SCL-90) was administered to assess criterion validity. We assessed the relationship between the developed PASM-UF and the SCL-90 via a correlation analysis. Cronbach's alpha was used to assess internal consistency for reliability. Results: We included five items, pain, lack of appetite, fatigue (tiredness), disturbed sleep, and anxiety, in the final version of the PASM-UF. Data were collected from 228 patients. Cronbach's alpha was 0.745, whereas the correlation coefficient between SCL-90 and PASM-UF was 0.345 ( p  < 0.001). The total PASM-UF scores were significantly higher in patients whose SCL-90 scores were ≥160 compared to those with <160 (9.85 ± 9.07 vs. 4.01 ± 5.15, p  = .002). Those who did not complete the SCL-90 reported lower PASM-UF scores than those who did (2.33 ± 3.27 vs. 4.67 ± 5.99, p  = .006). Patients reported significantly lower PASM-UF scores postoperatively than preoperatively (2.95 ± 4.18 vs. 3.92 ± 4.90, p  = .002). Conclusions: The PASM-UF is a valid, reliable, and sensitive scale for assessing perioperative anxiety levels among women with uterine fibroids. Statistical analysis suggests that it is also an effective instrument for scientific research. Key Message: We developed a brief scale to assess anxiety in perioperative patients with uterine fibroids. In addition, the scale monitored the anxiety levels at multiple frequencies and did not increase burden on the patients. The scale has been proven to be effective, reliable, and highly sensitive.